2019
DOI: 10.1155/2019/7013758
|View full text |Cite
|
Sign up to set email alerts
|

The Lipodystrophy Syndrome in HIV-Infected Children under Antiretroviral Therapy: A First Report from the Central Africa

Abstract: Background. Despite the high prevalence of the HIV/AIDS, few studies focused on the prevalence of lipodystrophy in pediatric HIV patients on antiretroviral therapy (ARV) in sub-Saharan African countries. The aim of this study was to assess the prevalence and to identify the risk factors of metabolic disorders related to ARV therapy in this population. Methods. A cross-sectional study was completed in Kinshasa, the Democratic Republic of Congo. HIV-infected children aged between six and 18 years on ARV were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…The presence of metabolic disorders is related to the high lipid levels in the blood associated with hypersensitivity reactions to drugs so that it can lead to therapeutic failure from ART 2 . Genetic determination of the APOC3 gene has a large impact in the selection of therapeutic regimens and predicts the failure of HAART drugs in children with HIV infection in Africa 8,9 . Highly active ART brings about significant improvement, improving the quality of life of HIV children 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of metabolic disorders is related to the high lipid levels in the blood associated with hypersensitivity reactions to drugs so that it can lead to therapeutic failure from ART 2 . Genetic determination of the APOC3 gene has a large impact in the selection of therapeutic regimens and predicts the failure of HAART drugs in children with HIV infection in Africa 8,9 . Highly active ART brings about significant improvement, improving the quality of life of HIV children 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Being this condition also associated to hypothalamic tumors, in young children presenting with lipodystrophy, it is fundamental to evaluate also the possibility of CNS tumors, especially when history and clinical evaluation do not fit for other types of LD [2,30]. In addition, lipodystrophy associated to insulin therapy in diabetic patients and HIV-related lipodystrophy has to be considered [33][34][35][36][37]. Among lipodystrophic lesions in patients on insulin therapy, lipohypertrophy (LH) due to inappropriate injection habits is the most common [33,38].…”
Section: Other Causes Of Acquired Lipodystrophymentioning
confidence: 99%
“…For what concerns HIV, current antiretroviral therapy (ART) has been associated with body fat redistribution and metabolic abnormalities, both in adults and in children [35,37]. Recently, Tshamala et al performed a cross-sectional study in Kinshasa (Democratic Republic of Congo) and recruited 80 HIV-infected children on ARV therapy, 80 non-infected children and 65 HIV-infected antiretroviral therapy-naïve children [36]. The authors reported a not statistically different frequency of lipoatrophy between HIV-infected children on ARV therapy (16.3%) and HIV-infected antiretroviral therapy-naïve children (21.5%); while a significantly higher rate of LH and hypercholesterolemia was noted in HIV-children on ARV compared to the controls (p < 0.05) [36].…”
Section: Other Causes Of Acquired Lipodystrophymentioning
confidence: 99%
“…Associations between abnormal body fat distribution and pediatric HIV disease have been established in various studies (60)(61)(62). HIV infection itself is a factor that causes lipodystrophy syndrome in children who are being treated with antiretroviral medications (63) and could refer to abnormal fat accumulation (lipohypertrophy) or localized loss of fatty tissue (lipoatrophy) (64).…”
Section: Nutritional Status Of Hiv-infected Infants and Childrenmentioning
confidence: 99%